A Study on the Parental involvement on academic achievement of XI STD Students - Arthi, R.; Selvakumar, Y. Stanly (International Journal of Advanced Research in Peace, Harmony and Education; Vol 8 No 1 (2023): International Journal of Advanced Research in Peace, Harmony & Education, 2023)
Education is the basic for the advancement of the society. The more knowledgeable the general population of the entire masses are, the more cultivated the general public may be. For the most part, family has the duty of making the kids gainful to the society. This above-mentioned study investigated the parental involvement in their children’s educational atmosphere that is, the academic achievement on the children of class xi. When parents get involved in studies, children will be able to do better in school and they go to better heights in their life. Several studies have critically examined parental involvement and student achievement; Infact very few studies analyze the effect of it on the student’s academic performance. This research study has to take a leap ahead and, has entangled both parental involvement and academic achievement and overall performance of the students. The aim of the study is twofold, the first one to analyze whether the parental involvement has an impact on the academic achievement on the students and the latter is with respect to whether the academic achievement of the XI standard students varies with regard to their gender, residing locality, stream of study, medium of instruction, parental occupation and qualification and the family type.